Tinjauan Yuridis Terhadap Penegakan Hukum, Rehabilitasi, dan Eksekusi Pidana di Indonesia - Desya Arianti; Jumadil Jumadil; Fuad Nur (Jurnal Ilmu Sosial dan Humaniora, 2026)
Narcotics crime has evolved into one of the most complex forms of contemporary crime, characterized by its transnational network, sophisticated modus operandi, and significant social impact. The aim of this study is to analyse the dynamics of narcotics crime law enforcement in Indonesia from three distinct perspectives: the application of restorative justice, the effectiveness of medical rehabilitation for drug abuse victims and addicts, and the enforcement of capital punishment for narcotics offenders. This study employs a normative legal approach supported by a literature assessment of relevant academic publications and legal statutes. The results indicate that narcotics crime can no longer be approached solely through repressive punishment, but requires a differentiated approach depending on the position of the perpetrator. Drug users and victims of abuse are more appropriately addressed through medical rehabilitation, whereas perpetrators involved in large-scale narcotics trafficking networks remain subject to strict law enforcement, including the threat of capital punishment. However, the implementation of capital punishment faces obstacles such as the absence of a definite time limit for execution and the availability of legal remedies. This study concludes that an integrated approach combining restorative justice, medical rehabilitation, and firm law enforcement against organized crime networks is necessary to effectively address narcotics crime as a form of contemporary crime in Indonesia.